Research in social movements, conflicts and change. Vol. 42 - Coy, Patrick G. (Bingley, U.K. : Emerald Publishing Limited, 2018)
"Research in Social Movements, Conflicts and Change" has now published continuously for over 40 years, and this volume continues its tradition of delivering data-driven and multi-method research by scholars who constantly push theory forward. Covering a compelling range of subjects, this important collection begins by addressing the critically important dimensions of the relationships that social movements, their activists, and their organizations have with the state and other institutions. It then moves on to examine three movements linked by frame and discourse analysis, before concluding with a survey of the biographical trajectory of activism. The contributions focus on a number of topical and crucially important issues, including, among others: environmental activism in China, the Black Lives Matter movement, the 2011 uprising in Tunisia, and Russian opposition movements. With a strong contributor team and a confident style, this volume is a significant addition to the RSMCC series and will be of great interest to those working and researching within the social movement field.
Prelims -- Introduction -- Social movements and their institutional relations -- Frames and discourses in conflicts and social movements -- Activist start-up and withdrawal -- Index.
Includes index.
Print version record
Keywords: Social movements; Social conflict; Social psychology; Social Science -- Research; Social issues & processes